Exploring the Diversity of Mechanisms Associated With Plant Tolerance to Virus Infection - Paudel, Dinesh Babu; Sanfaçon, Hélène (Frontiers in Plant Science, 2018)
Tolerance is defined as an interaction in which viruses accumulate to some degree without causing significant loss of vigour or fitness to their hosts. Tolerance can be described as a stable equilibrium between the virus and its host, an interaction in which each partner not only accommodate trade-offs for survival but also receive some benefits (e.g. protection of the plant against super-infection by virulent viruses; virus invasion of meristem tissues allowing vertical transmission). This equilibrium, which would be associated with little selective pressure for the emergence of severe viral strains, is common in wild ecosystems and has important implications for the management of viral diseases in the field. Plant viruses are obligatory intracellular parasites that divert the host cellular machinery to complete their infection cycle. Highjacking/modification of plant factors can affect plant vigour and fitness. In addition, the toxic effects of viral proteins and the deployment of plant defence responses contribute to the induction of symptoms ranging in severity from tissue discoloration to malformation or tissue necrosis. The impact of viral infection is also influenced by the virulence of the specific virus strain (or strains for mixed infections), the host genotype and environmental conditions. Although plant resistance mechanisms that restrict virus accumulation or movement have received much attention, molecular mechanisms associated with tolerance are less well understood. We review the experimental evidence that supports the concept that tolerance can be achieved by reaching the proper balance between plant defence responses and virus counter-defences. We also discuss plant translation repression mechanisms, plant protein degradation or modification pathways and viral self-attenuation strategies that regulate the accumulation or activity of viral proteins to mitigate their impact on the host. Finally, we discuss current progress and future opportunities towards the application of various tolerance mechanisms in the field.